Biogreen Synthesis of Carbon Dots for Biotechnology and Nanomedicine Applications - Chan, Kok Ken; Yap, Stephanie Hui Kit; Yong, Ken-Tye (Nano-Micro Letters, 2018)
Over the past decade, carbon dots have ignited a burst of interest in many different fields, including nanomedicine, solar energy, optoelectronics, energy storage, and sensing applications, owing to their excellent photoluminescence properties and the easiness to modify their optical properties through doping and functionalization. In this review, the synthesis, structural and optical properties, as well as photoluminescence mechanisms of carbon dots are first reviewed and summarized. Then, we describe a series of designs for carbon dot-based sensors and the different sensing mechanisms associated with them. Thereafter, we elaborate on recent research advances on carbon dot-based sensors for the selective and sensitive detection of a wide range of analytes, including heavy metals, cations, anions, biomolecules, biomarkers, nitroaromatic explosives, pollutants, vitamins, and drugs. Lastly, we provide a concluding perspective on the overall status, challenges, and future directions for the use of carbon dots in real-life sensing. Highlights: 1 Introduction to carbon dots: properties, photoluminescence mechanism, and synthesis. 2 The design principles of carbon dot-based sensors and sensing mechanisms. 3 The versatility of carbon dots for the sensing of different analytes.